Soundwalking in virtual urban ambiances. Applying Game Engine Technologies in soundscape study - Valerio Signorelli (Ambiances)
The purpose of this research is to develop a tool able to enhance the visual representation of urban environments through the auditory stimuli and dynamic components. Since the sixties, various qualitative studies have been conducted in order to reveal the role of the sonic environment in defining the physical and psychological wellbeing of the city-dwellers. Nevertheless, in urban planning practices and current regulations the sonic environment is often considered in term of pollutant (noise pollution) that need to be treated by applying quantitative approaches such as noise control strategies. The cause of this contradiction can be attributed, among other factors, by the lack of tools able to qualitatively describe the urban ambiances. The innovative technologies tested in this research, such as online location-based services and game engine systems, were used to develop devices able to provide a temporal and multimodal representation of the city. These devices explore the transposition, in a virtual environment, of the soundwalk conceived as an efficient technique for analyzing the sensible forms of the urban environment. The test of these digital tools allowed us to highlight limits and potentialities of the technologies employed.